UNVEILING THE NEXUS: PROFESSIONAL COMMITMENT, WELL-BEING, AND TECHNOLOGY ADOPTION AMONG ECONOMICS EDUCATORS" - Juliana, Novela; Yulastri, Resti; Akmal; Arjanto, Paul (Journal of Economic Education, 2025)
This study investigates the relationship between teachers’ professional commitment, well-being, and their adoption of technology in educational settings, focusing on economics educators in Indonesia. As digital integration becomes increasingly essential in teaching, understanding the internal factors that shape educators’ readiness to use technology is crucial. Using Structural Equation Modeling (SEM) with Partial Least Squares (PLS), the study analyzes questionnaire data from 207 respondents to examine both direct and indirect effects among the key variables. The findings show that teacher well-being significantly enhances professional commitment, which in turn positively influences technology adoption. Additionally, self-development and pedagogical competence contribute meaningfully to teachers’ willingness to integrate technological tools into their instructional practices. These results extend the application of the Unified Theory of Acceptance and Use of Technology (UTAUT-1) by demonstrating how psychological and professional factors shape technology acceptance in educational contexts. Overall, the study provides important insights for improving teacher training programs, strengthening institutional support, and promoting effective digital integration in economics education. By emphasizing the interconnected roles of well-being, commitment, and competence, the research highlights pathways for enhancing pedagogical innovation and supporting sustainable educational development